Isolation methods of human and bovine adipose tissue derived stem cells - Fhataheya, Buang; Mukhzeer, Mohamad Shahimin, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/